P041 Targeting fibroblast activation protein in Crohn's disease intestinal strictures restores balanced deposition of extracellular matrix and reduces fibrosis. (16th January 2018) - Truffi, M; Sorrentino, L; Monieri, M; Mazzucchelli, S; Fociani, P; Sampietro, G M; Di Sabatino, A; Corsi, F
Abstract: Background: Bowel fibrosis is a chronic and progressive process characterised by excessive deposition of extracellular matrix (ECM) and imbalance between matrix metalloproteinases (MMPs) and their tissue inhibitors (TIMPs). This phenomenon represents a severe end-stage of some chronic inflammatory disorders such as Crohn's disease (CD), for which effective medical therapy is currently unavailable. Key players in CD fibrosis are intestinal myofibroblasts, whose activation and function are characterised by a number of elements, including the overexpression of fibroblast activation protein (FAP). We investigated the effects of FAP-targeted therapy on ECM remodelling in CD strictures ex vivo. Methods: Stenotic and non-stenotic bowel specimens were collected from ileal resections from 30 patients with fibrostenotic CD. Mucosal myofibroblasts were isolated and analysed for FAP expression by immunoblotting and flow cytometry. Bowel tissues were treated with anti-FAP antibody in culture medium; total soluble collagen, type I and III collagen, TIMP-1 and MMPs were measured in the supernatants, while inflammatory and fibrogenic pathways were investigated by immunoblotting on tissue protein extracts. Effects of anti-FAP treatment on the migratory potential and survival of intestinal myofibroblasts were evaluated by wound healing assay and Annexin V staining, respectively. Results: Stenotic CD myofibroblasts showed upregulation of FAP protein. Treatment with anti-FAP antibody induced a significant dose-dependent decrease in collagen production by stenotic bowel tissues, while it did not affect non-stenotic bowel areas. Treatment on CD strictures particularly reduced type I collagen and TIMP-1 production, and did not change MMP-3 and MMP-12 secretion. Moreover, anti-FAP treatment on myofibroblasts from stenotic CD mucosa inhibited TIMP-1 expression and enhanced myofibroblast migration, without affecting their survival. Conclusions: Our results demonstrated a role for FAP targeting in reducing type I collagen and TIMP-1 production by CD strictures ex vivo, thus suggesting a valuable reconstitution of ECM homeostasis in fibrostenotic CD.